"I Was Learning Every Step of the Way": Student Perceptions About a New Required Foundational Master of Public Health Program Planning Course. (March 2023) - Stolow, Jeni; Lederer, Alyssa
Objective: Tulane University School of Public Health and Tropical Medicine created a program planning course required for all master of public health (MPH) students to address the revised 2016 Council on Education for Public Health (CEPH) foundational competencies. The objective of this study was to examine students' feedback on this new class based on their reflective writing. Methods: Students across 3 class sections during 3 semesters (fall 2018, spring 2019, and fall 2019) wrote a reflection paper as a final assignment about their course experience (N = 102). We conducted a conventional qualitative content analysis of deidentified student responses to systematically examine themes in the overarching areas of what students found valuable about the course and what they would want to be improved. We calculated frequency counts of themes to further contextualize the findings. Results: Students found the following aspects of the course valuable: a positive perception shift toward program planning (93.1%), new transferable career skills (87.3%), the course format (77.5%), course content (69.6%), working in teams (52.0%), course assignments (47.1%), and the instructional team (31.4%). Critiques included the following: more support for course assignments (39.2%), challenges of working in teams (27.5%), aspects of the course format (25.5%), gaps in course content (19.6%), and wanting more consultations with the instructional team (5.9%). About 14% of students stated there was nothing or little they would change about the course. Conclusion: Overall, the course received positive feedback from students. They identified several valuable course components and areas that could be enhanced, which we have worked to improve. We offer the course as a potential model for how schools and programs of public health can meet the 2016 CEPH competencies.